Cleaning material silicon dioxide for toothpaste and preparation method thereof
By using nanosilica modified polyethoxyethylene ether surfactant and quaternary ammonium modified chitosan in toothpaste, combined with silica sol, the problem of insufficient cleaning effect of existing toothpaste is solved. Achieve more efficient teeth cleaning effects and stability.
Patent Information
- Application Number
- CN202411780601.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
AI Technical Summary
The silica used in existing toothpastes has insufficient cleaning effect and cannot effectively improve the cleaning effect of the tooth surface.
Nanosilicon dioxide modified polyethoxyethylene ether surfactant and quaternary ammonium modified chitosan modify nanosilicon dioxide particles, combined with silica sol, synergistically through the modification of surfactant and modified nanosilicon dioxide particles Effect, improve the cleaning effect of toothpaste.
It significantly improves the cleaning effect of toothpaste, can more effectively remove dirt and bacteria on the surface of teeth, reduce the formation of plaque, and improves the stability and fluidity of toothpaste.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon dioxide, in particular to silicon dioxide, a cleaning material for toothpaste, and a preparation method thereof. Background Art
[0002] Toothpaste is a paste-like substance used to clean teeth and maintain oral hygiene. Toothpaste contains ingredients such as abrasives, moisturizers, and surfactants. Abrasives are the most basic ingredients in toothpaste and are used to remove dirt and plaque on the surface of teeth. Common abrasives include calcium carbonate, calcium hydrogen phosphate, silicon dioxide, and aluminum hydroxide. These ingredients help remove food residues and pigment deposits on the surface of teeth through physical friction. Among them, silicon dioxide particles are fine, have low friction values, and have less wear on tooth enamel, so they are widely used in toothpaste. For example, patent CN118005023A discloses a method for preparing silicon dioxide and toothpaste. The toothpaste made from silicon dioxide prepared by this method is not easy to agglomerate and has good stability, but its cleaning effect is not improved. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a cleaning material silicon dioxide for toothpaste and a preparation method thereof, which has a good cleaning effect.
[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a cleaning material silica for toothpaste, comprising the following components by weight: 14-18 parts by weight of nano-silica modified polyethoxylated ether surfactant, 17-20 parts by weight of quaternary ammonium salt modified chitosan modified nano-silica particles, and 5-8 parts by weight of silica sol.
[0005] Preferably, the preparation method of the nano-silicon dioxide modified polyethoxylated ether surfactant comprises the following steps: (1) Dissolve 5-8 parts by weight of vinyl triethoxysilane in an ethanol solution and hydrolyze it, then add 7-9 parts by weight of nano-silica aerogel, anhydrous ethanol and deionized water into a beaker, stir for 8-10 minutes, add the hydrolyzed vinyl triethoxysilane thereto, heat to 58-62° C., stir for 2-3 hours, filter, wash and dry after the reaction is completed to obtain silane coupling agent modified nano-silica; (2) adding 6-8 parts by weight of silane coupling agent-modified nano-silica and 8-10 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then adding 0.5-0.7 parts by weight of benzoin dimethyl ether photoinitiator thereto, irradiating with 365 nm ultraviolet light at 35-42° C., centrifuging after irradiation, washing and drying to obtain intermediate 1; (3) 5-8 parts by weight of the intermediate 1 and 0.4-0.6 parts by weight of the catalyst are added to the autoclave, the temperature is raised to 78-82°C, low boiling point substances and water in the system are removed in vacuo, and after nitrogen replacement, the temperature is raised to 150-170°C, 4-7 parts by weight of ethylene oxide are added, and the induction reaction is started. When the pressure drops to 0.1-0.15 MPa, 9-13 parts by weight of ethylene oxide are continuously added to make the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 75-80°C, and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica modified polyoxyethylene ether surfactant.
[0006] Preferably, the mass fraction of the ethanol solution in step (1) is 30-35%.
[0007] Preferably, the ultraviolet light irradiation time in step (2) is 2.5-3.5 hours.
[0008] Preferably, the catalyst in step (3) is sodium hydroxide.
[0009] Preferably, the method for preparing the quaternary ammonium salt-modified chitosan-modified nano-silica particles comprises the following steps: S1. Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, add 3-chloropropyltrimethoxysilane dropwise thereto, reflux at 78-85°C for 15-16h, and after the reaction is completed, cool, wash and dry to obtain intermediate 2; S2. 6-9 parts by weight of chitosan are dissolved in an acetic acid solution, stirred to dissolve, 0.2-0.5 parts by weight of 1-hydroxybenzotriazole initiator is added, and then 9-12 parts by weight of intermediate 2 are added, nitrogen is introduced, and the reaction is carried out at 75-80 ° C for 16-18h. After the reaction is completed, freeze-dried to obtain quaternary ammonium salt-modified chitosan; S3. Add 7-9 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 10-15 minutes, add 5-7 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution thereto, react at 80-82°C for 4.5-5 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 12000-13000 rpm, wash and dry to obtain quaternary ammonium salt-modified chitosan-modified nano-silica particles.
[0010] Preferably, the mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane in S1 is 1:1.04-1.08.
[0011] Preferably, the mass fraction of the acetic acid solution in S2 is 0.8-1.2%.
[0012] Preferably, the mass fraction of the hydrochloric acid solution in S3 is 2.8-3%.
[0013] Preferably, the preparation method of the cleaning material silica for toothpaste is: adding nano-silica modified polyethoxylated ether surfactant, quaternary ammonium salt modified chitosan modified nano-silica particles, and silica sol into a reactor, stirring at a speed of 1200-1400 rpm for 10-12 minutes to obtain the cleaning material silica for toothpaste.
[0014] 3. Beneficial technical effects The invention obtains cleaning material silica for toothpaste by adding nano silica modified polyethoxylated ether surfactant, quaternary ammonium salt modified chitosan modified nano silica particles and silica sol into a reactor and stirring.
[0015] The hydrolyzed vinyl triethoxysilane reacts with nano-silica aerogel to obtain nano-silica modified by silane coupling agent and introduce alkenyl groups. The alkenyl groups in the nano-silica modified by silane coupling agent react with the mercapto groups in 8-mercapto-1-octanol to introduce a long hydrophobic chain containing hydroxyl groups to obtain intermediate 1. Intermediate 1 polymerizes with ethylene oxide at high temperature to obtain nano-silica modified polyethoxyalkylene ether surfactant. N,N-dimethylglycine reacts with 3-chloropropyltrimethoxysilane to obtain intermediate 2 and introduce carboxyl groups. The carboxyl groups in intermediate 2 react with amino groups in chitosan to obtain quaternary ammonium salt modified chitosan. The methoxy groups in the quaternary ammonium salt modified chitosan react with the hydroxyl groups on the surface of nano-silica after hydrolysis to obtain quaternary ammonium salt modified chitosan modified nano-silica particles.
[0016] In the nano-silica modified polyethoxylated ether surfactant, silane coupling agent is used to replace the hydroxyl group on the surface of nano-silica, which reduces the surface energy of nano-silica and the interaction force between particles, making it easier for silica particles to be evenly dispersed in the cleaning material, increasing the contact area between the cleaning material and the dirt, and enhancing the cleaning effect; during the cleaning process, the hydrophobic groups of the polyethoxylated ether molecules will adsorb to the surface of the dirt particles, and the hydrophilic groups will interact with water molecules to form a stable colloidal dispersion system. The dirt particles are wrapped inside the micelles and washed away with the water flow, thereby achieving to achieve a cleaning effect; the silane coupling agent modified nano-silica and polyethoxylated ether exert a synergistic effect to further improve the cleaning effect; in the quaternary ammonium salt modified chitosan modified nano-silica particles, the cations in the quaternary ammonium salt molecules can adsorb negatively charged bacteria through electrostatic forces, hydrogen bonds and hydrophobic binding with protein molecules, thereby removing bacteria and reducing the formation of dental plaque; the quaternary ammonium salt is grafted onto chitosan to increase the positive charge density and thereby improve the cleaning effect; the quaternary ammonium salt modified chitosan and nano-silica exert a synergistic effect to make the cleaning material have a stronger cleaning effect. DETAILED DESCRIPTION
[0017] Example 1 (1) Dissolve 5 parts by weight of vinyl triethoxysilane in an ethanol solution and hydrolyze it, wherein the mass fraction of the ethanol solution is 30%, then add 7 parts by weight of nano-silica aerogel, anhydrous ethanol, and deionized water into a beaker, stir for 8 minutes, then add the hydrolyzed vinyl triethoxysilane, heat to 58°C, stir for 2 hours, filter, wash and dry after the reaction is completed, and obtain silane coupling agent modified nano-silica; (2) Add 6 parts by weight of silane coupling agent modified nano-silica and 8 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then add 0.5 parts by weight of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 35° C. for 2.5 h, centrifuge, wash and dry to obtain intermediate 1; (3) 5 parts by weight of the intermediate 1 and 0.4 parts by weight of a sodium hydroxide catalyst are added to an autoclave, the temperature is raised to 78° C., low-boiling substances and water in the system are removed in vacuo, and after nitrogen replacement, the temperature is raised to 150° C., 4 parts by weight of ethylene oxide are added to start an induction reaction, and when the pressure drops to 0.1 MPa, 9 parts by weight of ethylene oxide are continuously added to keep the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 75° C., and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica-modified polyoxyethylene ether surfactant; (4) Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, then dropwise add 3-chloropropyltrimethoxysilane, wherein the mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane is 1:1.04, and reflux at 78°C for 15h. After the reaction is completed, cool, wash and dry to obtain intermediate 2; (5) Dissolve 6 parts by weight of chitosan in acetic acid solution, wherein the mass fraction of the acetic acid solution is 0.8%, stir to dissolve, add 0.2 parts by weight of 1-hydroxybenzotriazole initiator, and then add 9 parts by weight of intermediate 2, pass nitrogen protection, react at 75°C for 16 hours, and after the reaction is completed, freeze-dry to obtain quaternary ammonium salt modified chitosan; (6) Add 7 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 10-15 minutes, add 5 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution, wherein the mass fraction of the hydrochloric acid solution is 2.8%, react at 80°C for 4.5 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 12000 rpm, wash and dry to obtain quaternary ammonium salt-modified chitosan modified nano-silica particles; (7) 14 parts by weight of nano-silica-modified polyethoxylated ether surfactant, 17 parts by weight of quaternary ammonium salt-modified chitosan-modified nano-silica particles, and 5 parts by weight of silica sol were added into a reactor and stirred at 1200 rpm for 10 min to obtain cleaning material silica for toothpaste.
[0018] Example 2 (1) 8 parts by weight of vinyl triethoxysilane was dissolved in an ethanol solution and hydrolyzed, wherein the mass fraction of the ethanol solution was 35%, and then 9 parts by weight of nano-silica aerogel, anhydrous ethanol and deionized water were added to a beaker, stirred for 10 minutes, and then the hydrolyzed vinyl triethoxysilane was added thereto, the temperature was raised to 62° C., and stirred for 3 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain silane coupling agent modified nano-silica; (2) Add 8 parts by weight of silane coupling agent-modified nano-silica and 10 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then add 0.7 parts by weight of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 42° C. for 3.5 h, centrifuge, wash and dry to obtain intermediate 1; (3) 8 parts by weight of the intermediate 1 and 0.6 parts by weight of a sodium hydroxide catalyst are added to an autoclave, the temperature is raised to 82° C., low-boiling substances and water in the system are removed in vacuo, and after nitrogen replacement, the temperature is raised to 170° C., 7 parts by weight of ethylene oxide are added, and an induction reaction is started. When the pressure drops to 0.15 MPa, 13 parts by weight of ethylene oxide are continuously added to keep the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 80° C., and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica-modified polyoxyethylene ether surfactant; (4) Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, then dropwise add 3-chloropropyltrimethoxysilane, wherein the mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane is 1:1.08, and reflux at 85°C for 16 hours. After the reaction is completed, cool, wash and dry to obtain intermediate 2; (5) dissolving 9 parts by weight of chitosan in an acetic acid solution with a mass fraction of 1.2% of the acetic acid solution, stirring to dissolve, adding 0.5 parts by weight of 1-hydroxybenzotriazole initiator, and then adding 12 parts by weight of intermediate 2, passing nitrogen protection, reacting at 80° C. for 18 h, and after the reaction, freeze-drying to obtain quaternary ammonium salt modified chitosan; (6) Add 9 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 15 minutes, add 7 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution, wherein the mass fraction of the hydrochloric acid solution is 3%, react at 82°C for 5 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 13000 rpm, wash and dry to obtain quaternary ammonium salt modified chitosan modified nano-silica particles; (7) 18 parts by weight of nano-silica-modified polyethoxylated ether surfactant, 20 parts by weight of quaternary ammonium salt-modified chitosan-modified nano-silica particles, and 8 parts by weight of silica sol are added into a reactor and stirred at 1400 rpm for 12 minutes to obtain cleaning material silica for toothpaste.
[0019] Example 3 (1) 6 parts by weight of vinyl triethoxysilane was dissolved in an ethanol solution and hydrolyzed, wherein the mass fraction of the ethanol solution was 32%, and then 8 parts by weight of nano-silica aerogel, anhydrous ethanol and deionized water were added to a beaker, stirred for 9 minutes, and then the hydrolyzed vinyl triethoxysilane was added thereto, the temperature was raised to 60°C, and stirred for 2.5 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain silane coupling agent modified nano-silica; (2) adding 7 parts by weight of silane coupling agent-modified nano-silica and 9 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then adding 0.6 parts by weight of benzoin dimethyl ether photoinitiator thereto, irradiating with 365 nm ultraviolet light at 38° C. for 3 h, centrifuging after irradiation, washing and drying to obtain intermediate 1; (3) 7 parts by weight of the intermediate 1 and 0.5 parts by weight of a sodium hydroxide catalyst are added to an autoclave, the temperature is raised to 80° C., low-boiling substances and water in the system are removed in vacuo, and after nitrogen substitution, the temperature is raised to 160° C., 5 parts by weight of ethylene oxide are added, and an induction reaction is started. When the pressure drops to 0.12 MPa, 11 parts by weight of ethylene oxide are continuously added to keep the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 78° C., and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica-modified polyoxyethylene ether surfactant; (4) Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, then dropwise add 3-chloropropyltrimethoxysilane, wherein the mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane is 1:1.06, and reflux at 82°C for 15.5h. After the reaction is completed, cool, wash and dry to obtain intermediate 2; (5) Dissolve 8 parts by weight of chitosan in acetic acid solution, wherein the mass fraction of the acetic acid solution is 1%, stir to dissolve, add 0.3 parts by weight of 1-hydroxybenzotriazole initiator, and then add 10 parts by weight of intermediate 2, pass nitrogen protection, react at 78°C for 17 hours, and after the reaction is completed, freeze-dry to obtain quaternary ammonium salt modified chitosan; (6) Add 8 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 12 minutes, add 6 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution, wherein the mass fraction of the hydrochloric acid solution is 2.9%, react at 81°C for 4.8 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 12500 rpm, wash and dry to obtain quaternary ammonium salt-modified chitosan modified nano-silica particles; (7) 16 parts by weight of nano-silica-modified polyethoxylated ether surfactant, 18 parts by weight of quaternary ammonium salt-modified chitosan-modified nano-silica particles, and 7 parts by weight of silica sol were added into a reactor and stirred at 1300 rpm for 11 minutes to obtain cleaning material silica for toothpaste.
[0020] Example 4 (1) Dissolve 5 parts by weight of vinyl triethoxysilane in an ethanol solution and hydrolyze it, wherein the mass fraction of the ethanol solution is 30%, then add 7 parts by weight of nano-silica aerogel, anhydrous ethanol, and deionized water into a beaker, stir for 8 minutes, then add the hydrolyzed vinyl triethoxysilane, heat to 58°C, stir for 2 hours, filter, wash and dry after the reaction is completed, and obtain silane coupling agent modified nano-silica; (2) Add 6 parts by weight of silane coupling agent modified nano-silica and 8 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then add 0.5 parts by weight of benzoin dimethyl ether photoinitiator, irradiate with 365 nm ultraviolet light at 35° C. for 2.5 h, centrifuge, wash and dry to obtain intermediate 1; (3) 8 parts by weight of the intermediate 1 and 0.6 parts by weight of a sodium hydroxide catalyst are added to an autoclave, the temperature is raised to 82° C., low-boiling substances and water in the system are removed in vacuo, and after nitrogen replacement, the temperature is raised to 170° C., 7 parts by weight of ethylene oxide are added, and an induction reaction is started. When the pressure drops to 0.15 MPa, 13 parts by weight of ethylene oxide are continuously added to keep the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 80° C., and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica-modified polyoxyethylene ether surfactant; (4) Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, then dropwise add 3-chloropropyltrimethoxysilane, wherein the mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane is 1:1.08, and reflux at 85°C for 16 hours. After the reaction is completed, cool, wash and dry to obtain intermediate 2; (5) Dissolve 8 parts by weight of chitosan in acetic acid solution, wherein the mass fraction of the acetic acid solution is 1%, stir to dissolve, add 0.3 parts by weight of 1-hydroxybenzotriazole initiator, and then add 10 parts by weight of intermediate 2, pass nitrogen protection, react at 78°C for 17 hours, and after the reaction is completed, freeze-dry to obtain quaternary ammonium salt modified chitosan; (6) Add 8 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 12 minutes, add 6 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution, wherein the mass fraction of the hydrochloric acid solution is 2.9%, react at 81°C for 4.8 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 12500 rpm, wash and dry to obtain quaternary ammonium salt-modified chitosan modified nano-silica particles; (7) 16 parts by weight of nano-silica-modified polyethoxylated ether surfactant, 18 parts by weight of quaternary ammonium salt-modified chitosan-modified nano-silica particles, and 7 parts by weight of silica sol were added into a reactor and stirred at 1300 rpm for 11 minutes to obtain cleaning material silica for toothpaste.
[0021] Comparative Example 1 Compared with Example 4, the difference in this comparative example is that no nano-silicon dioxide-modified polyethoxylated ether surfactant is added.
[0022] Comparative Example 2 Compared with Example 4, the difference in this comparative example is that no quaternary ammonium salt-modified chitosan-modified nano-silica particles are added.
[0023] Patients with at least one symptom such as yellow teeth, tooth stains and bad breath were selected as test subjects, with an age distribution of 35-55 years old. They were randomly divided into 6 groups, each group corresponding to an embodiment or a comparative example, with 30 people in each group. Each experimenter used the toothpaste cleaning material silica to brush his teeth every day, once in the morning and once in the evening, each time for 2-5 minutes. There was no significant difference in the amount used by each person each time. The method of use was consistent with that of ordinary toothpaste, and 15 days was a course of treatment. The testers scored according to their own feelings. The scoring standard adopts a 10-point system, 1 point is the worst, that is, there is no change before and after use, 10 points are the best, that is, the symptoms are significantly improved after use, and the score results of each group are averaged, and the breath test instrument is used to measure the breath value of each experimenter after a course of treatment. The results are shown in Table 1: Table 1: Cleaning effectiveness test.
[0024]
[0025] It can be seen from Table 1 that Examples 1-4 of the present invention have better cleaning effects on teeth than Comparative Examples 1-2.
[0026] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A cleaning material silicon dioxide for toothpaste, characterized in that: The invention comprises the following components by weight: 14-18 parts by weight of nano silicon dioxide modified polyethoxylated ether surfactant, 17-20 parts by weight of quaternary ammonium salt modified chitosan modified nano silicon dioxide particles, and 5-8 parts by weight of silica sol.
2. The cleaning material silica for toothpaste according to claim 1, characterized in that The preparation method of the nano-silicon dioxide modified polyethoxylated ether surfactant comprises the following steps: (1) Dissolve 5-8 parts by weight of vinyl triethoxysilane in an ethanol solution and hydrolyze it, then add 7-9 parts by weight of nano-silica aerogel, anhydrous ethanol and deionized water into a beaker, stir for 8-10 minutes, add the hydrolyzed vinyl triethoxysilane thereto, heat to 58-62° C., stir for 2-3 hours, filter, wash and dry after the reaction is completed to obtain silane coupling agent modified nano-silica; (2) adding 6-8 parts by weight of silane coupling agent-modified nano-silica and 8-10 parts by weight of 8-mercapto-1-octanol to N,N-dimethylformamide solvent, and then adding 0.5-0.7 parts by weight of benzoin dimethyl ether photoinitiator thereto, irradiating with 365 nm ultraviolet light at 35-42° C., centrifuging after irradiation, washing and drying to obtain intermediate 1; (3) 5-8 parts by weight of the intermediate 1 and 0.4-0.6 parts by weight of the catalyst are added to the autoclave, the temperature is raised to 78-82°C, low boiling point substances and water in the system are removed in vacuo, and after nitrogen replacement, the temperature is raised to 150-170°C, 4-7 parts by weight of ethylene oxide are added, and the induction reaction is started. When the pressure drops to 0.1-0.15 MPa, 9-13 parts by weight of ethylene oxide are continuously added to make the system ethylene oxide pressure constant. After the ethylene oxide feeding is completed, the autoclave is cooled to 75-80°C, and the ethylene oxide gas in the reaction system is removed in vacuo to obtain a nano-silica modified polyoxyethylene ether surfactant.
3. The cleaning material silica for toothpaste according to claim 2, characterized in that: The mass fraction of the ethanol solution in step (1) is 30-35%.
4. The cleaning material silica for toothpaste according to claim 2, characterized in that: The ultraviolet light irradiation time in step (2) is 2.5-3.5 hours.
5. The cleaning material silica for toothpaste according to claim 2, characterized in that: The catalyst in step (3) is sodium hydroxide.
6. The cleaning material silica for toothpaste according to claim 1, characterized in that: The method for preparing the quaternary ammonium salt-modified chitosan-modified nano-silica particles comprises the following steps: S1. Add N,N-dimethylglycine and anhydrous ethanol to a three-necked flask and stir, add 3-chloropropyltrimethoxysilane dropwise thereto, reflux at 78-85°C for 15-16h, and after the reaction is completed, cool, wash and dry to obtain intermediate 2; S2. 6-9 parts by weight of chitosan are dissolved in an acetic acid solution, stirred to dissolve, 0.2-0.5 parts by weight of 1-hydroxybenzotriazole initiator is added, and then 9-12 parts by weight of intermediate 2 are added, nitrogen is introduced, and the reaction is carried out at 75-80 ° C for 16-18h. After the reaction is completed, freeze-dried to obtain quaternary ammonium salt-modified chitosan; S3. Add 7-9 parts by weight of nano-silica particles to anhydrous ethanol, ultrasonically disperse for 10-15 minutes, add 5-7 parts by weight of chitosan modified with silane quaternary ammonium salt, stir and mix, then dropwise add hydrochloric acid solution thereto, react at 80-82°C for 4.5-5 hours, and after the reaction is completed, centrifuge the nano-silica at a speed of 12000-13000 rpm, wash and dry to obtain quaternary ammonium salt-modified chitosan-modified nano-silica particles.
7. The cleaning material silica for toothpaste according to claim 6, characterized in that: The mass ratio of N,N-dimethylglycine to 3-chloropropyltrimethoxysilane in S1 is 1:1.04-1.
08.
8. The cleaning material silica for toothpaste according to claim 6, characterized in that: The mass fraction of the acetic acid solution in S2 is 0.8-1.2%.
9. The cleaning material silica for toothpaste according to claim 6, characterized in that: The mass fraction of the hydrochloric acid solution in S3 is 2.8-3%.
10. A method for preparing the cleaning material silicon dioxide for toothpaste according to any one of claims 1 to 9, characterized in that: The preparation method of the cleaning material silica for toothpaste comprises: adding nano-silica-modified polyethoxylated ether surfactant, quaternary ammonium salt-modified chitosan-modified nano-silica particles and silica sol into a reactor, stirring at a speed of 1200-1400 rpm for 10-12 minutes, and obtaining the cleaning material silica for toothpaste.
Citation Information
Cited By
Preparation method of mildew-proof plate
CN121105159A